Randomised controlled trial of the effect of evidence based information on women's willingness to participate in cervical cancer screening. Issue 8 (25th July 2003) - Adab, P; Marshall, T; Rouse, A; Randhawa, B; Sangha, H; Bhangoo, N
Abstract : Study objectives: To assess whether providing women with additional information on the pros and cons of screening, compared with information currently offered by the NHS, affects their intention to attend for screening. Design: Randomised controlled trial. Participants were randomly assigned to receive either the control, (based on an NHS Cervical Screening Programme leaflet currently used), or the intervention leaflet (containing additional information on risks and uncertainties). Setting: Three general practices in Birmingham. Participants: 300 women aged 20 to 64 attending the practices during a one month period. Main outcome measures: Intention to attend for screening. Main results: 283 women (94.3%) completed the study. Fewer women in the intervention (79%) than the control group (88%) expressed intention to have screening after reading the information leaflet (difference between groups 9.2%, 95% confidence intervals (CI) 3.2% to 21.7%). The crude odds ratio (OR) and 95% CI was 0.50 (0.26 to 0.97). After adjusting for other factors, the trend persisted (OR 0.60, 95% CI 0.28 to 1.29). Having a previous Pap smear was the only significant predictor of intention to have screening (adjusted OR 2.54, 95% CI 1.03 to 6.21). Subgroup analysis showed no intervention effect in intended uptake between women at higher and lower risk of cervical cancer (p=0.59). Conclusions: Providing women with evidence based information on the risks, uncertainties, and the benefits of screening, is likely to deter some, but not differentially those at higher risk.